The Influence of the Guided Inquiry Learning Model on Students' Critical Thinking Skills in Fisheries Subjects in Grade IV of SD Inpres 2 Besusu - Nuraini, Nuraini; Sari, Dewi Anita; Zulnuraini, Zulnuraini; Aras, Nurul Fitriah; Khairunnisa, Khairunnisa (Journal of Educational Sciences, 2025)
This study aims to analyze the learning outcomes of students whose learning uses the Guided Inquiry learning model on students' critical thinking skills in the science course in grade IV of SD Inpres 2 Besusu. This study uses a quantitative approach with a pre-experimental experimental design in the form of a pretest-postest design for one group. Sampling was carried out using a random sample extraction technique. The data collection technique uses learning outcome tests, observation sheets and interviews. The data analysis used in this study is descriptive and face-to-face statistical analysis. Based on the results of a study on the Influence of the Guided Inquiry Learning Model on the Critical Thinking Ability of Social Science Students of Grade IV SD Inpres 2 Besusu on the Influence of Social Science Learning Outcomes of Students of SD Inpres 2 Besusu on the Influence of Social Science Learning Outcomes of Students of SD Inpres 2 Besusu Class IV, the researcher can draw the conclusion that there is an influence of the use of the Guided Inquiry learning model on the influence of learning outcomes Social Studies Students Grade IV SD Inpres 2 Besusu.